Identifikasi Karakteristik akuifer dan Potensi Air Tanah untuk Irigasi pada Sub DAS Data Kabupaten Wajo Sulawesi Selatan - Suhardi Suhardi (Jurnal Agritechno, 2020)
Sustainable groundwater extraction can be achieved if there is a balance between the amount of groundwater extracted and recharge. The ability of aquifers to release groundwater that affects groundwater extraction and recharge depends on aquifer characteristics. Therefore, aquifer characteristics need to be known so that the amount of extraction does not exceed groundwater recharge. This study aims to determine the position, thickness, type, specific yield and hydraulic conductivity of aquifers and identify catchment areas as sources of groundwater and groundwater potential. This research was conducted by interpolating lithology data and measuring aquifer hydraulic conductivity by pumping test methods. Hydraulic conductivity values were processed using Solver Add Ins in Microsoft Excel to get optimal conductivity values. The source of groundwater recharge was predicted based on a flownet of groundwater surface contour data and groundwater potential calculated using the Darcy’s approach. The results showed that the hydraulic conductivity in the study area was 16.13 m / day, the specific result was 0.32 with aquifer in the form of sand. Based on the flownet, the source of recharge comes from the western side of the watershed which flows eastward with a potential of 14,517 m3 / day ≈ 168.02 lt / sec.